Construção e desconstrução da lei: a arena legislativa e o trabalho escravo - Lilia Carvalho Finelli (2016)
.The law can be constructed and de-constructed with a simple touch from the legislator. It is a need to knowing that process in the democratic debate, avoiding throwbacks in rights previsions without society acknowledging it. Work in analogous conditions to slave, as defined on article 149 of Brasils Criminal Code, presuppose the offense of distinct kinds of legal goods: freedom of movement and/or dignity. Therefore, four hypothesis are defined in this complex crime type: forced labor, servitude, degrading conditions of work and exhausting workdays journeys. These last two, that offend dignity, are considered as outside the concept, deserving a revision. However, the historical and legal review demonstrates the importance of their regulation and the need of having them as crimes, especially for Labor Law. This dissertation is concerned about unveiling actual bills that are processing inside Brasils Chamber of Deputies and Federal Senate, especially those that remove from article 149 the degrading conditions and exhausting workdays journeys, evidencing the attempt of de- constructing the law, removing rights. As it will be demonstrated, those intents go against Brasils national laws so as international laws and its progressive constructing, leading to rights throwback.